2019
DOI: 10.3390/ijerph16091650
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution in Surface Water of Urban Lakes in Changsha, China

Abstract: As emerging pollutants, microplastics have attracted the attention of scholars from all over the world. However, there is a lack of research on freshwater areas, even in densely populated urban areas. This study investigated eight urban lakes in Changsha, China. It was found that microplastic concentrations ranged from 2425 ± 247.5 items/m3 to 7050 ± 1060.66 items/m3 in the surface water of research areas and the maximum concentration was found in Yuejin Lake, a tourist spot in the center of the city. Anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 41 publications
3
27
1
5
Order By: Relevance
“…more than thousands of km) and have been found in geographically remote regions (i.e. polar areas and waterbodies on undeveloped plateaus) (Lusher et al, 2015;Horton et al, 2017a;Baptista Neto et al, 2019;C. Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…more than thousands of km) and have been found in geographically remote regions (i.e. polar areas and waterbodies on undeveloped plateaus) (Lusher et al, 2015;Horton et al, 2017a;Baptista Neto et al, 2019;C. Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The type of black particle analysed in our study was identified as polyamide, however it is not sufficient to make a valid decision, further detailed studies need to be carried out. µ-Raman method has been used frequently and successfully in MP identification (Anger et al, 2018;Gündoğdu, 2018;Wen et al, 2018;Xiong et al, 2018;Yin et al, 2019). In many previous studies, MP determination has been made only by visual identification (Desforges et al, 2014;Miranda & de Carvalho-Souza, 2016;Rochman et al, 2015), however, many recent studies have added spectrophotometric methods (µ-Raman or FTIR) in addition to microscopic examination Tsang et al, 2017;Wen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, if the sampling was conducted during the summer period, an increase in the amount of MP was likely due to the decrease in pond surface area. However, majority of the studies were conducted with a single sampling and widely available in the literature both for freshwater and marine ecosystems Yin et al, 2019;Scopetani et al, 2019;Wang et al, 2019;Egessa et al, 2020). Moreover, there is a possibility of error in the microscope identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have no conflict of interest. (Zhao et al, 2020a) The Qiantang River and its tributaries, Hangzhou 54-3379 23%-74% Fibre 87 (Xia et al, 2020) Dong Lake, Wuhan City, Hubei Province 7400-29600 95.04% Fibre 88 (Feng et al, 2020) The Qilian mountains, Northeast part of Tibetan Plateau 66.67-773 25%-100% Fibre 89 (Yan et al, 2019) Guangzhou urban section of Pearl River 8725-53250 7% Film 90 (Tan et al, 2019) the Feilaixia Reservior, Beijiang River 0.28-1.1 15.73% Film 91 (Yin et al, 2019) Meixi Lake, Changsha City Mean: 2563 46% Fragment 92 (Yin et al, 2019) Nianjia Lake, Changsha City Mean: 5600 23% Fragment…”
Section: Disclosure Statementmentioning
confidence: 99%